THE TREND TOWARDS MODERNIZATION AND ITS RELATIONSHIP TO THE EFFICIENCY OF JOB PERFORMANCE AMONG PHYSICAL EDUCATION AND SPORTS TEACHERS IN SECONDARY SCHOOLS IN THE RAMADI EDUCATION DIRECTORATE - Suad Hasan Saeed; Yaseen Ali Khalaf (Proximus Journal Publishing, 2024)
The importance of the study lies in investigating and searching for the most important basic factors in the adequacy of the teacher's job performance in line with the rapid technological development. The study aimed to identify the trend towards modernization and its relationship to the adequacy of job performance among physical education and sports teachers in secondary schools affiliated with the Ramadi Education Directorate. The descriptive approach was used in the correlation method in a sample of 100 male and female teachers, and their percentage of the total population was reached (40%). After distributing the modernization and job performance adequacy scales to the teachers, the results were collected and processed statistically. The researcher concluded that there is a positive moral relationship between the trend towards modernization and the adequacy of work performance among physical education and sports teachers. Therefore, the researcher recommends updating the competencies of physical education and sports teachers for their role in improving and developing the efficiency of the performance of physical education and sports teachers.
Keywords: Modernization of life skills; adequacy of job performance; physical education and sports teachers; secondary schools